14.7k views
4 votes
This question is confusing me can someone help me figure out how to solve

This question is confusing me can someone help me figure out how to solve-example-1
User Lucasg
by
4.8k points

1 Answer

2 votes

Answer:

(f ○ g)(- 6) = 1

Explanation:

Find g(- 6) from graph then use this value to find f, that is

When x = - 6 then g(- 6) = 4 ← from graph

When x = 4 then f(4) = 1 ← from graph

Thus (f ○ g)(- 6) = 1

User Snifff
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.